Household Customers’ Satisfaction towards Solar Energy in Rupandehi District - Bhandari, Dansi Ram; Jnawali, Govinda (Butwal Campus Journal, 2023)
This paper aims to evaluate household customer satisfaction towards solar energy in Rupandehi district, Nepal. In order to address research issues, the study used questionnaire survey among 105 respondents during February to April, 2023. Multiple linear regression model was used to evaluate household customers’ satisfaction based on characteristics of the product, customer services, contribution of the product and government support criteria. The research results showed that characteristics of the solar panel product (efficiency, durability convenient to use, price and quality) are highly concerning satisfaction criterion. Based on the results obtained of this study, it is concluded that there are high opportunities to manufacturers and solar panel service providers to keep their household customers satisfied by providing effective after sales service. Although, contribution of the solar panel energy towards energy needs of household customers is the less concerning criterion. There is large area for expansion to be made to increase solar energy market through the proper government initiation. The main implication of this study is that manufacturers should attention while designing, pricing and producing solar energy products to satisfy their customers for a long time. The results obtained may be useful to solar panel manufacturers, service providers, government authorities and researchers.